2015
DOI: 10.3390/cancers8010002
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Mechanisms of Sp1-Dependent Transcriptional Regulation Potentially Involved in the Adaptive Response of Cancer Cells to Oxygen-Deficient Conditions

Abstract: The inside of a tumor often contains a hypoxic area caused by a limited supply of molecular oxygen due to aberrant vasculature. Hypoxia-inducible factors (HIFs) are major transcription factors that are required for cancer cells to adapt to such stress conditions. HIFs, complexed with the aryl hydrocarbon receptor nuclear translocator, bind to and activate target genes as enhancers of transcription. In addition to this common mechanism, the induction of the unfolded protein response and mTOR signaling in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…We found p53 and SP1 might bind to DMR near CREB5 , which were validated by ChIP-qPCR. SP1 is a widely expressed transcription factor and plays critical roles in transcriptional regulation by binding to GC-rich cis-elements in many promoter regions [ 39 ]. SP1 can also interact with other transcription factors like methyl transferases, acetylases/de-acetylases, and other chromatin modifying molecules, which are involved in numerous cellular processes including cell growth, apoptosis, immune responses and so on [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found p53 and SP1 might bind to DMR near CREB5 , which were validated by ChIP-qPCR. SP1 is a widely expressed transcription factor and plays critical roles in transcriptional regulation by binding to GC-rich cis-elements in many promoter regions [ 39 ]. SP1 can also interact with other transcription factors like methyl transferases, acetylases/de-acetylases, and other chromatin modifying molecules, which are involved in numerous cellular processes including cell growth, apoptosis, immune responses and so on [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we look further into the binding capacity of HIF1α with other cofactors, like Sp1, CBP, p300, and we found that NLGP prevents colocalization of HIF1α with CBP, p300 and Sp1 but not with Sp3, which can competitively target HIF1α and Sp1 binding. Sp1 and Sp3 compete for binding to the HRE region as they share more than 90% sequence homology (39)(40)(41). Consequently, we observed significant less binding of active HIF1α complex with HRE region.…”
Section: Discussionmentioning
confidence: 69%
“…However, the effect of miR-125b on drug resistance in colorectal cancer cells and the underlying mechanism by which miR-125b modulates CD248 expression still need to be investigated. Specificity protein 1 (Sp1), a basic transcriptional regulator for numerous genes, is usually related to carcinogenesis [18,19]. Sp1 binding to the promoter region of the CD248 gene activates its expression under high cell density culture conditions [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Specificity protein 1 (Sp1), a basic transcriptional regulator for numerous genes, is usually related to carcinogenesis [18,19]. Sp1 binding to the promoter region of the CD248 gene activates its expression under high cell density culture conditions [18,20]. According to the results of a miRNA microarray using chemoresistant colon cancer cells and a search using the web-based miRNA prediction software TargetScan (http://www.targetscan.org/), we found that Sp1 could be a target gene of miR-125b-5p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation